2009
DOI: 10.2807/ese.14.39.19343-en
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing rubella outbreak in Bosnia and Herzegovina, March-July 2009 - preliminary report

Abstract: O n g O i n g r u b e l l a O u t b r e a k i n b O s n i a a n d H e r z e g O v i n a , M a r c H -J u ly 2 0 0 9 -p r e l i M i n a r y r e p O r t A Novo (ano@who.ba) 1 ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…However, the relation of this lineage to the circulating strains in Brazil cannot be determined. Genotype 2B viruses were previously known to circulate in China, India, South Korea, and South Africa [WHO, 2005;WHO, 2006;Caidi et al, 2008;Rajasundari et al, 2008] before being introduced into some countries in Europe [Jin and Thomas, 2007;Novo et al, 2009;D'Agaro et al, 2010;Vauloup-Fellous et al, 2010] and South America [Valinotto et al, 2009]. The variation observed in this study reflected the molecular characteristics of RVs in population with low vaccine coverage.…”
Section: Discussionmentioning
confidence: 51%
“…However, the relation of this lineage to the circulating strains in Brazil cannot be determined. Genotype 2B viruses were previously known to circulate in China, India, South Korea, and South Africa [WHO, 2005;WHO, 2006;Caidi et al, 2008;Rajasundari et al, 2008] before being introduced into some countries in Europe [Jin and Thomas, 2007;Novo et al, 2009;D'Agaro et al, 2010;Vauloup-Fellous et al, 2010] and South America [Valinotto et al, 2009]. The variation observed in this study reflected the molecular characteristics of RVs in population with low vaccine coverage.…”
Section: Discussionmentioning
confidence: 51%
“…More recently, the circulation of genotype 1j was documented in Spain, possibly introduced by persons from Latin America [Martinez‐Torres et al, 2009]. Genotype 2B is autochthonous in the Far East, namely Japan and Korea, and in South Africa, although it is now considered an imported European genotype [Jin and Thomas, 2007; Novo et al, 2009]. In Italy, genotyping of RUBVs isolated during three consecutive outbreaks (1991–1997) showed that clade 1 viruses were predominant, while only two strains belonging to clade 2 were detected during the epidemic of 1994 [Zheng et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Genotype 2B viruses are known to have circulated in China, India, South Korea, and South Africa [WHO, 2005, 2007; Caidi et al, 2008; Rajasundari et al, 2008; Zhu et al, 2010] before being introduced in some European countries [Jin and Thomas, 2007; Novo et al, 2009; D'Agaro et al, 2010; Vauloup‐Fellous et al, 2010] and South America [Valinotto et al, 2009; Gallegos et al, 2011]. The fact that genotype 2B was not detected in the Americas before 2006 may indicate importation from Europe or Asia where this genotype is endemic.…”
Section: Discussionmentioning
confidence: 99%